Sensory and Bioactive Properties Response to Reformulation and Processing of Java-Tea-Based Functional Drink: a Review - A’yuni, Qurrata; Wijaya, Christofora Hanny; Mastuti, Titri S.; Sukarno (Journal Akademik Universitas Swiss German, 2022)
Java-tea-based (Orthosiphon aristatus B. Miq) functional drink is reported to have privileges, mainly its physiological functions and bioactive properties such as antioxidant activity and antihyperglycemic ability. Java-tea-based functional drinks contain bioactive compounds from natural materials, including java-tea leaves, ginger, sappan-wood, curcuma, lime, and kaffir lime. Several innovations and challenges have been carried out during its development, affecting the drinks' quality and stability. The stability of the beverage, especially in the aspects of sensory and bioactive properties, is still considered inferior. This review focuses on the formulation and processing technology conducted from 2007 to 2019. In the case of the reformulation, it showed that the addition of kaffir lime extract, lime extract, and flavor enhancer could improve the sensory properties in terms of aroma and taste. Furthermore, the changes in the specific java-tea plants' variety as the main ingredient and replacing the sucrose with non-sucrose sweeteners increased the bioactive properties. Recently, the formula has been enriched with a red fruit oil emulsion to improve the drink's appearance due to contains abundant carotenoid pigments. However, the addition also created another hurdle, particularly in the flavor sensory aspect and emulsion stability. In the case of processing, applying microencapsulation and nanoencapsulation in java-tea drinks has increased the bioactive properties, especially antioxidant activity, and antihyperglycemic, and also improved the product's stability which prolonged the shelf life. The development of java-tea-based functional drinks might become a milestone to reference other similar product development.